Evaluation of the degree of integration of primary health care with specialized care in the model of local health unit experienced in Portugal - Nunes, Alexandre Morais (Saúde e Sociedade, 2021)
The integration of primary health care with the specialized care provided in hospitals was an important challenge to the Portuguese health system. Initiated in 1999 via a pilot experience, this integration took place with the creation of Local Health Units. All assistance (primary and hospital care) in the same region came to depend on a single management team, with equal rules and operating models. Although the model has several years and there are currently eight Local Health Units, the truth is that this model has not been objectively evaluated. Considering this objective, a study was published in the journal Health and Society that evaluated the degree of integration of Primary Health Care in a small city in the Health Care Network, whose evaluation methodology fits perfectly in the objective of this study. Thus, this method of evaluation was adopted by means of a matrix with 25 indicators accompanied by evaluation parameters and scored from 0 to 3. Questionnaires were applied to health professionals of the Local Health Units in Portugal to measure the degree of integration. The final score (degree of integration) was estimated by the ratio between the sum of the points received and expected, multiplied by 10. The results show a national integration score of 7.03, which indicates the good integration between primary and specialized care.